Penghalang Pernikahan (Rabaib / Anak Bawaan Istri) - Teguh Ramadhan; Raihan Nasa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Marriage in Islamic law is governed by various provisions related to mahram, one of which is the prohibition of marrying a wife’s child from a previous marriage, known as